HSP47 at the Crossroads of Thrombosis and Collagen Dynamics: Unlocking Therapeutic Horizons and Debates - Smadja, David M.; Chocron, Alberto F.; Abreu, M. Marc (TH Open, 2025)
Heat shock protein 47 (HSP47), a collagen-specific molecular chaperone encoded by the SERPINH1 gene, has emerged as a groundbreaking focus in thrombosis research. Recent findings published in “Science” have revolutionized our understanding of thrombosis, identifying HSP47 as a critical mediator in a new thrombosis target for treatment. This discovery not only unveils a novel pathway in thrombosis but also opens new avenues for therapeutic intervention. HSP47's significance extends beyond thrombosis, influencing pathological processes such as fibrosis and cancer. In fibrosis, its upregulation promotes collagen deposition, while its dysregulation in osteogenesis imperfecta (OI) Type X underscores the protein's indispensable role in collagen biosynthesis. The therapeutic challenge lies in balancing HSP47 inhibition to reduce fibrotic burden without impairing its essential physiological functions. In cancer, HSP47 plays dual roles. It supports tumor progression through collagen stabilization and metastasis facilitation while contributing to tissue repair under hyperthermia treatment combined with radiotherapy or chemotherapy. However, its overexpression can exacerbate tumor aggressiveness via mechanisms such as angiogenesis and epithelial–mesenchymal transition.This review emphasizes the pivotal discovery of HSP47's thrombogenic role and its broader implications in disease biology. These findings mark a paradigm shift in thrombosis research and underscore the potential of HSP47 as a target in diverse pathological contexts, from platelet-driven diseases to fibrotic and oncological disorders.
Keywords: heat shock protein 47; collagen; thrombosis; angiogenesis; cancer therapy; hyperthermia